The Effects of Two Different Reading Acceleration Training Programs on Improving Reading Skills of Second Graders. Issue 4 (18th May 2016) - Nevo, Einat; Brande, Sigalit; Shaul, Shelley
Abstract : It has been well established that poor reading skills in the first grades of primary school can lead to poor reading skills in all coming years. A reading acceleration program (RAP) known to improve reading skills in adults and children with and without reading difficulties (RD) was tested for its effect on children in second grade with standard reading skills. The influence of the RAP on improving all reading skills—decoding, fluency, and reading comprehension—was examined. Seventy-nine children in second grade were divided into two study groups and one control group. Each study group received a training program that emphasizes reading skills: decoding, fluency, and comprehension were trained at the levels of words and sentences in Version A and at the levels of words and paragraphs in Version B. Both programs significantly improved reading skills compared with the control group that was not trained: Group A improved word fluency whereas Group B improved accuracy measures (word, pseudo-word, and text). Both training groups showed significantly greater improvement over time than the control group on reading comprehension. We conclude that a RAP training that combines words, sentences, and paragraphs is the most effective for improving reading skills.